Development of Technology-Based Islamic Religious Education Media and Learning Resources - Azieda, Nur Aeni Angger Rifqi; Yanti, Yanti; Hayani, Aida; Musyrifah, Farida (DAS Institute, 2025)
This study aims to analyze the professional competency needs of elementary school teachers in Yogyakarta. Using the Literature Study method, this study collects data from various literatures related to the development of teacher professional competencies, as well as an analysis of the priority competency needs index among elementary school teachers. The results of the study indicate that the development of information technology can be utilized to support more interactive and dynamic teaching in Islamic religious education, which has been proven to increase student engagement and understanding. Application-based learning technology, online platforms, and other digital media enable more equitable and relevant access to religious education for the younger generation. With the integration of technology, Islamic religious education is expected to be more interesting and effective in achieving learning objectives in the digital era.